Faktor Pendorong Respon Komunitas Pondok Pesantren Madura Terhadap Bank Syariah - Iskandar Iskandar (ITB AAS INDONESIA Surakarta, 2019)
Abstract: This study aimed to determine how the community of Islamic boarding schools responds to Islamic banks and what factors that were drived the response of the boarding school community to Islamic banks.The procedure of data collection in this study was obtained using the interview method, and supported by documentation and observation, and then the data was analyzed to obtain conclusions and verification. The results of this study explained that there were two groups of Islamic boarding school community responses to Islamic banks. first, the community is responsive to Islamic banks, and second, the community is less responsive to Islamic banks. the factors of islamic boarding school community to Islamic banks include: the community's view of bank interest law, the policy of head master of the Islamic boarding school, the introduction and dissemination of Islamic banking, access to Islamic banks, and the relationship between the values ​​of Islamic boarding schools. Keywords: Response, Islamic Boarding School Community, Islamic Bank Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana respon komunitas pondok pesantren terhadap bank syariah dan faktor pendorong respons komunitas pondok pesantren terhadap bank syariah. Prosedur pengumpulan data dalam penelitian ini diperoleh dengan menggunakan metode wawancara, dan didukung oleh dokumentasi dan observasi, kemudian data dianalisa untuk diperoleh kesimpulan dan verifikasi. Hasil penelitian menjelaskan bahwa terdapat dua kelompok respon komunitas pondok pesantren terhadap bank syariah. Yaitu: komunitas responsif terhadap bank syariah dan komunitas kurang responsif terhadap bank syariah. Sedangkan faktor pendorong respon komunitas pondok pesantren terhadap bank syariah antaralain: pandangan komunitas terhadap hukum bunga bank, kebijakan kiyai pimpinan pondok pesantren, pengenalan dan sosialisasi tentang perbankan syariah, akses terhadap bank syariah, keterkaitan antara nilai-nilai pondok pesantren dengan bank syariah. Kata kunci: Respon, Komunitas Pondok pesantren, Bank syariah